(untitled) (Homiletic, 2021)
Preaching on nationwide trauma was a less developed theological-homiletical theme of Korean Protestant churches, although Korean society has been traumatized by consecutive national crises during the twentieth century. Despite the fundamental cause of suffering, the unbearable trauma of victims has been interpreted as divine punishment based on early missionary tradition, which is based on an orthodox theodicy. Korean preaching, therefore, revealed its deficiency because it has not only failed its pastoral role to provide a secure haven for victims, but also has not preached a message of justice to the corrupted sociopolitical structures in its prophetic role. This paper suggests the significance of lament as a theological-homiletical strategy that proposes a hermeneutic dynamic of compassion and resistance in response to a national trauma.